Socialization of Introduction to Understanding The World of The Financial Profession for Students At State 9 Vocational High School, West Jakarta - Sormin, Feber; Tarmidi, Deden (EQUATOR SINAR AKADEMIA, 2024)
Purpose of activity PkM with title Socialization introduction Understanding the World of Professionals in the field finance For students at vocational schools for increase interests, hopes and interests For dream So expert profession field finance . Constitution Number 4 of 2023 concerning Financial Sector Support and Support (PPSK) consists of from Public Accountant (AP), Accountant Practicing (AB), Actuary, Public Appraiser, Tax Consultant , Notary , Legal Consultant , Financial Services Sharia Expert ; and other professions determined by the Ministry, Institution, or supervisory and supervisory authority profession related , necessary introduced my friend interest .Problems : 1). Many Accounting Vocational School students However only few have​ objective become expert Profession Finance like Accountant besides profession finance other. 2). Current PPPK statement Socialization of Professional Services Finance in Bandar Lampung delivered No A little students who have low interest, and yet understand How become a profession reliable finances.​ 3). Guard sustainability need power profession field finance in accordance development. The method used is : 1). Extension methods, 2). Question and answer method, 3 ). Demonstration Method . Devotion public This held especially for student School Intermediate Vocational School (SMK) Negeri 9, West Jakarta. Activity results: With extension method past presentation, Q & A, Demonstration​ past the practitioner explains experience his profession direct to student /I has be a Solution: 1). Produce interest and motivation vocational school students who have objective For become power expert profession finance, 2). Vocational school students who want to working in the professional world Finance understand better​ major studies his lectures, 3). give knowledge in practice about profession finance including required competencies​ owned To use add interest interest take Major Accounting, 4). Participant more know method For become a power expert / profession in the field of Financial Services, 5). Activity This has give contribution input to party government, academics, and parties other.